Chemical deterioration and physical instability of food and beverages - Skibsted, Leif H. (Leif Horsfelt); Risbo, Jens.; Andersen, Mogens L. (Oxford : Woodhead Pub. ; Boca Raton : CRC Press, 2010)
"For a food product to be a success in the marketplace, it must be stable throughout its shelf-life. Quality deterioration due to chemical changes and alterations in condition due to physical instability are not always recognised, yet can be just as problematic as microbial spoilage. This book provides an authoritative review of key topics in this area." "Chapters in Part I focus on the chemical reactions which can negatively affect food quality, such as oxidative rancidity, and their measurement. Part II reviews quality deterioration associated with physical changes, such as moisture loss, gain and migration, crystallisation and emulsion breakdown. Contributions in the following section outline the likely effects on different foods and beverages, including bakery products, fruit and vegetables, ready-to-eat meals, dairy products and wine." "With contributions from leaders in their fields, Chemical deterioration and physical instability of food and beverages will be an essential reference work for R&D and QA staff in the food industry and researchers with an interest in this subject."--BOOK JACKET.
Oxidative rancidity in foods and food quality / J. Velasco, C. Dobarganes and G. Márquez-Ruiz -- Protein oxidation in foods and food quality / M.N. Lund and C.P. Baron -- The Maillard reaction and food quality deterioration / C. Perez-Locas and V.A. Yaylayan -- Flavor deterioration during food storage / G. Reineccius -- Light-induced quailty changes in foods and beverages / M.L. Anderson and L.H. Skibsted -- Moisture loss, gain and migration in foods and its impact on food quality / G. Roudaut and F. Debeaufort -- Crystallization in foods and food quality deterioration / R.K. Bund and R.W. Hartel -- Structural and mechanical properties of fats and their implications for food quality / M.F. Peyronel, N.C. Acevedo and A.G. Marangoni -- Emulsion breakdown in foods and beverages / S. Ghosh and D. Rousseau -- Gelatinization and retrogradation of starch in foods and its implications for food quailty / A-C. Eliasson -- Syneresis in food gels and its implications for food quality / S. Mizrahi -- Understanding, detecting and preventing taints in food / D. Kilcast -- Chemical and physical deterioration of bakery products / S.P. Cauvain and L.S. Young -- Chemical and physical deterioration of bulk oils and shortenings, spreads and frying oils / F.D. Gunstone and S. Martini -- Chemical processes responsible for quality deterioration in fish / C. Jacobsen ... [et al.] -- Chemical and physical deterioration of wine / A.L. Waterhouse and R.J. Elias -- Postharvest chemical and physical deterioration of fruit and vegetables / A.K. Thompson -- Enzymatic deterioration of plant foods / N.A.M. Eskin and M. Aliani -- Stability of vitamins during food processing and storage / P. Berry Ottaway -- Chemical and physical deterioration of frozen foods / N.E. Zaritzky -- Chemical deterioration and physical instabilty in ready-to-eat meals and catered foods / P.G. Creed -- Chemical deterioration and physical instability of food powders / P. Intipunya and B.R. Bhandari -- The effect of non-meat ingredients on quality parameters in meat and poultry / M.N. O'Grady and J.P. Kerry -- Chemcical deterioration and physical instability of dairy products / G. Mortensen ... [et al.].
Includes bibliographical references and index.
Keywords: Food -- Analysis; Food -- Quality